If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -1(3x + 5) = 0 Reorder the terms: 7x + -1(5 + 3x) = 0 7x + (5 * -1 + 3x * -1) = 0 7x + (-5 + -3x) = 0 Reorder the terms: -5 + 7x + -3x = 0 Combine like terms: 7x + -3x = 4x -5 + 4x = 0 Solving -5 + 4x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 4x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + 4x = 0 + 5 4x = 0 + 5 Combine like terms: 0 + 5 = 5 4x = 5 Divide each side by '4'. x = 1.25 Simplifying x = 1.25
| x+0.04x= | | 18q-6q-11q+1=5 | | Z-5z=4z-6-z | | -c+2=6 | | -3(n-7)+6(4+3n)=-7n-1-n | | -28=-47-x | | 4p+1=13 | | 3.4=3.6+(-3.4c)+1.7c | | Z-4z=3z-3-z | | (x/5)-(x/4)=1 | | -6(2c-10)+22=c+4 | | -x-1=-1(-x-3) | | -2s+1=-7 | | 5x^2-25x+13=0 | | 47=28+x | | 5x+10+5x(-10)= | | 6-2j=4 | | -(7/8)r=6 | | 16x-5=11x-25 | | 30-3x=5x-18 | | 1.75t-4.5=7.74 | | 1.6=7.6-5(k+11) | | y=-2y | | x=28+(-47) | | 3z-6=-6z-15 | | 6x^3-21x^2-12x=0 | | -3(8p+6)-2(6-17p)=3(2+3p) | | 3x^2+7x+30=0 | | -0.9x+8.19=-0.7x+4.79 | | (3/11)z=-5 | | lnx-2ln=ln^4 | | 4(m-3)=8m-40 |